Optimalisasi Perumusan Strategi Konten Dan Target Pasar CV. Muara Rahmat - Benedictus Renee Sefiko Putra; Hendra Maulana (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to optimize content strategy formulation and target market determination for Batagor Selimut, a business unit under CV. Muara Rahmat, through the utilization of Instagram as a digital marketing platform. The main issues identified include visual inconsistency in content, low posting frequency, and weak brand recognition due to suboptimal management of profile elements. This research employed a descriptive qualitative approach through identification, initial observation, and analysis of the existing digital marketing practices. The results indicate that implementing consistent Instagram feed templates, establishing a regular posting schedule, and optimizing profile elements through bio updates and logo usage as visual identity significantly improved brand professionalism and brand image perception. Furthermore, defining the target market based on demographic, geographic, and psychographic segmentation provided clearer direction for content development and digital marketing communication strategies. The findings demonstrate that a structured content strategy and precise target market formulation can enhance the effectiveness of digital marketing for small and medium-sized enterprises.